The Role of Service Marketing Mix in Driving Patient Decisions to Choose Healthcare Services at Klinik Utama Pinang Sari 1 - Tesa Harianti Sidik; Sri Wulan Dari; Salwa Safira; Widad Salsabila; Saloma Klementina Saing; Wiwin Rianas; A. Rohendi (CV. Civiliza Publishing, 2026)
This study aims to deeply analyze and describe the role of the seven service marketing mix dimensions in driving patient decisions to select healthcare services at Klinik Utama Pinang Sari 1. A descriptive qualitative approach is used as the methodological foundation to capture genuine field narratives, utilizing interviews with patients, families, and clinic operational management as the primary source of information. Data analysis adopts an interactive model consisting of data reduction, data display, and conclusion drawing to ensure the validity of the research findings. Results indicate that the strategic packaging of product, price, place, promotion, people, process, and physical evidence significantly shapes positive public perceptions and acts as a primary stimulus for healthcare selection. Subjective experiences show that nurse friendliness, doctor clarity, digital queuing efficiency, clear tariff structures, and highway accessibility directly offer emotional satisfaction and security. Discussion reveals that the clinic’s competitive edge relies heavily on its ability to align promotional promises with high-quality real services on the ground. The functional integration of all marketing pillars successfully fosters long-term customer loyalty and secures the institution's position as a primary choice in a competitive private healthcare industry.